Pregnancy affects nevirapine pharmacokinetics: evidence from a CYP2B6 genotype-guided observational study. Issue 8 (August 2016) - Olagunju, Adeniyi; Bolaji, Oluseye; Neary, Megan; Back, David; Khoo, Saye; Owen, Andrew
Abstract : Objectives: Previous studies on nevirapine pharmacokinetics during pregnancy reported contradictory findings. Methods: The magnitude of pregnancy-induced changes in nevirapine pharmacokinetics was investigated in a genotype-guided study preceded by a pharmacogenetic association study of six genes involved in its disposition. Results: CYP2B6 516 G>T and 983 T>C were associated independently with plasma nevirapine concentrations in pregnant ( n =110) and postpartum ( n =122) women and were used for stratification. NR1I3 540C>T and P450 oxidoreductase 1508C>T were associated with lower and higher plasma concentrations in pregnant and postpartum women, respectively. In the intensive pharmacokinetic phase, apparent clearance (CL/ F ) was higher in pregnant ( n =31) than postpartum ( n =28) women ( P =0.022) and AUC0–12, C max and C min were significantly lower. When stratified on the basis of composite CYP2B6 516 G>T and 983 T>C genotypes, CL/ F was similar between pregnant ( n =6) and postpartum ( n =9) women with no variant alleles, but C min was below target (3400 ng/ml) in most patients in both groups. In women with one variant allele, clearance was 40.6% higher ( P =0.0009) and C min was below target in 58% (11/19) of pregnant and 0% (0/10) of postpartum women. Similarly, clearance was 51.7% higher ( P =0.008) in pregnant compared with postpartum women with two variant alleles. C min was below target in 50% (3/6) of pregnant and 0% (0/10) of postpartum women. Conclusion: Nevirapine exposure is significantly reduced during pregnancy. The pharmacodynamic consequences in patients at risk of suboptimal exposure and potential dose optimization strategies warrant further investigation.